Kedudukan Kurikulum Pendidikan Agama Islam di Sekolah dan Madrasah - Mansir, Firman; Abas, Sofyan (Indonesian Journal of Elementary Education and Teaching Innovation, 2024)
This study explains that in the national education curriculum, the fiqh curriculum is one of the derivatives of the national education goals. The fiqh curriculum becomes a branch of religious science whose supporters achieve national education goals, specifically in the character-building of students. The method used is a qualitative approach through library research so that in analyzing data with literature analysis. In facing an era like this, the teachings of norms are needed for students. So that the learning of fiqh acts as a guide for students in distinguishing a problem, good or bad in terms of religion and socially. Learning of fiqh in schools and madrasahs itself is based on government regulation (PP) number 55 of 2007. The regulation contains religious and religious education which is a derivative of the national education goals. Therefore, this research aims to describe the position of the Islamic Religious Education Curriculum (PAI) in learning Fiqh in the context of the National Curriculum. The legal basis of the Islamic Religious Education (PAI) curriculum in fiqh learning, as well as the learning function of fiqh in schools and madrasas The current and last context is the benefit of fiqh learning for students in responding to social life.